The Role of Attitude Towards Behavior and Utilitarian Benefit in Intention to Purchase Based on Theory of Planned Behavior in Generations Y and Z - Yayi Candradewi; Endy Gunanto Marsasi (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2023)
The fragrance industry is experiencing fast growth in Indonesia. The demand for perfume, particularly in the designer and luxury segments, is experiencing significant growth. This study aims to investigate the impact of ATB, PBC, utilitarian benefits, and marketing mix on intention to purchase. This study employs the TPB as its primary theoretical framework. The population comprises customers belonging to Generation Y and Generation Z. The data collecting strategy employs purposive sampling is incorporated into the nonprobability sampling strategy. The sample comprised 189 respondents. The results of the reliability test suggest that the data can be relied upon. The present study utilized a quantitative research methodology and conducted data analysis using IBM SPSS 27 and AMOS Graphic 24 software applications. The findings of the data analysis suggest that there is a statistically significant positive relationship between attitude and purchase intention. Additionally, the results suggest that utilitarian benefit has a notably favorable effect on behavior-related attitudes. Furthermore, the findings of this study suggest that there is no statistically significant relationship between the marketing mix and purchase intention. Consumers' propensity to purchase perfume may be affected by their utilitarian benefit and attitude.